Unveiling differences in biodiversity conservation efficiency across multi-level ecological networks under future climate change scenarios - Qiqi Liu; Tian Hang; Yunfei Wu; Youngkeun Song; Xiaolan Tang (Ecological Indicators)
Constructing ecological networks between protected areas is crucial for preventing further biodiversity loss. Considering the variations among protected areas, developing multi-level ecological networks can optimize resource allocation. However, the future effectiveness of these multi-level networks in protecting biodiversity remains unclear. In this study, we considered aspects including the distribution of endangered species, the impact of climate change, and human activity to identify ecological sources at different levels and established multi-level ecological corridors. We then evaluated the biodiversity conservation efficiency of multi-level ecological networks under future climate change scenarios. The results showed that high-priority ecological corridors are primarily concentrated in the southwestern part of the Yangtze River Delta, gradually extending eastward, while ecological corridors in the northern region are of relatively lower priority. Significant differences were also observed in the conservation efficiency of ecological networks at different levels. Under future climate change scenarios (SSP 126, 245, 370, and 585), smaller scale but higher-priority ecological networks (Level 1 and Level 2) demonstrated higher conservation efficiency, reaching 75.36% and 61.13%, respectively. In contrast, larger scale but lower-priority ecological networks (Level 3 and Level 4) had conservation efficiency below 50%. These results highlight that the prioritization of ecological networks should be considered during their construction and implementation, as it is essential to their future contributions to biodiversity conservation.